Common pathogenic aspects of diabetic retinopathy and nephropathy. Kidney transplantation and the course of diabetic retinopathy - I.V. Vorobyeva; L.K. Moshetova; A.V. Pinchuk; Е.V. Bulava; E.P. Delver; A.A. Belogurov (РМЖ "Клиническая офтальмология")
I.V. Vorobyeva1, L.К. Moshetova1, A.V. Pinchuk2–4, Е.V. Bulava1, Е.P. Delver5, А.А. Belogurov5 1Russian Medical Academy of Continuous Professional Education, Moscow,  Russian Federation 2N.V. Sklifosovskiy Research Institute for Emergency Medical Aid, Moscow, Russian Federation 3A.I. Evdokimov Moscow University of Medicine & Dentistry, Moscow, Russian Federation 4Research Institute of Public Health Organization and Medical Management, Moscow,  Russian Federation 5National Medical Research Center of Cardiology, Moscow, Russian Federation Epidemics of diabetes and its complications is a global threat to the health of human population. In 2040, the number of patients with diabetes is predicted to rise to 642 million. Diabetic retinopathy and nephropathy are the most dangerous complications. Chronic hyperglycemia is a major factor that determines the development and progression of microvascular complications of diabetes including retinopathy and nephropathy. Key biological pathogenic mechanisms of microvascular complications involve over-production of reactive oxygen species and activation of intracellular signaling pathways and their modulators. OCT angiography is a safe and informative early diagnostic tool to assess vascular retinal abnormalities and to monitor treatment efficacy. Proteinuria was long considered the gold standard to evaluate and monitor kidney functions. However, one-third of patients develop diabetic nephropathy in normal albuminuria. Degradation products of glomerular filtration barrier are thought to be perspective biomarkers of early diabetic nephropathy. End-stage renal disease requires kidney transplantation. In addition to the improvement of uremic syndrome, kidney transplantation favors the course of diabetic retinopathy. Keywords: diabetes, diabetic retinopathy, diabetic nephropathy, optical coherence tomography, OCT angiography, kidney transplantation. For citation: Vorobyeva I.V., Moshetova L.К., Pinchuk A.V. et al. Common pathogenic aspects of diabetic retinopathy and nephropathy. Kidney transplantation and the course of diabetic retinopathy. Russian Journal of Clinical Ophthalmology. 2021;21(2):90–95. DOI: 10.32364/2311-7729-2021-21-2-90-95.